(untitled) (Journal of Economic Research & Business Administration, 2015)
In modern conditions the internal control becomes an effective tool for the budgetary organization management. The increasing requirements to effective management stipulate the need in functional activization of the internal audit as an integral part of the internal control system in the organization. This requires qualitatively new theoretical comprehension of its essence and role in the public institution management. The article summarizes the concept, the purpose and the component elements of the internal control system. The definition and basic principles of internal audit are provided. The main purpose and the objectives of the internal audit are defined in terms of: general management system, management systems based on performance results, operating systems, internal control systems: financial transactions, property management. The above list of purposes of the internal audit confirms the multi-functional capacities of the internal audit. For a better understanding of the internal audit essence the fundamental principles on which it is based have been identified: the principle of independence and objectivity, the principle of confidentiality, the principle of professional competence